Customer intention towards Celcom broadband subscription: a study in Kota Bharu, Kelantan / Julaina Baistaman - Baistaman, Julaina (2008)
The aim of this study was to examine the factors influencing customers' intention to subscribe Celcom broadband in Kelantan state, focusing upon Kota Bharu. There are five factors that been studied, which were: attitude, subjective norms, knowledge, perceived usefulness and also price concern. Furthermore, this study also examined the relationship between demographic profiles and customers' intention. As Celcom had been choose as the unit of analysis for this study, researcher also interested to know about the strengths and weaknesses of Celcom's promotion with regards to its broadband and therefore, several suggestions could be provided to Celcom to improve their weaknesses and they may continue their current superb efforts on promoting the broadband to the customers. In collecting data, the researcher used both the secondary and primary data. Moreover, questionnaires had been used in order to get feedback from customers. Researcher had distributed 200 questionnaires to selected Celcom customers who not yet subscribe to Celcom broadband service. The data collected was then tested on its reliability, then further analyzed using frequency analysis, descriptive-mean tests, Chi Square and Pearson Correlation Coefficient was used to test the hypotheses in this study as well as regression analysis. The findings of this paper suggest that all the factors are significant factors for explaining customers' intention to subscribe to Celcom Broadband in Kota Bharu. However, none of the demographic profiles showed significant results in determining customers' intention. Based from the results obtained in this study, researcher suggests some recommendations that can help Celcom to improve their current strategies to increase the subscription of Celcom broadband service.